Kyrgyz Republic : 2009 Article IV Consultation and First Review Under the 18-Month Arrangement Under the Exogenous Shocks Facility; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the global crisis is hurting the Kyrgyz economy mainly through trade and remittance channels. Russia and Kazakhstan remain key trading partners and the main source of remittances for the Kyrgyz economy. Directors have commended the authorities on their prompt response to the crisis including a strong performance under the exogenous shocks facility arrangement. Directors have also welcomed the large financial support provided by the Russian Federation and the authorities' commitment to use this support in a medium-term budget framework.